Accumulating Disadvantages, Multiplying Inequalities: Biographies of Poverty in Mexico City. Issue 2 (4th March 2017) - Bayón, María Cristina
ABSTRACT: Emphasizing poverty as dynamic, multidimensional, and socially constructed, and based on in-depth interviews, this article analyzes the biographical experiences of residents of a highly deprived area in the periphery of México City. Departing from the family of origin and childhood, it goes through school, work, family, and migration experiences exploring processes leading to cumulative disadvantages during the life course, as well as tensions between opportunities and expectations, experiences, and discourses. Although allowing a better understanding of poverty as a process, a biographical approach also provides empirical evidences for dismantling public discourses that criminalize and blame the poor for their deprivations.